Application Progress of Aerogel / Inorganic Cementitious Composites in Building Thermal Insulation - Zeng Shuisheng; Zhang Jun; Zhang Huanlin; Li Rutian; Wang Guichao (E3S Web of Conferences, 2023)
In recent years, the problem of energy saving and consumption reduction in the construction industry has attracted more and more attention. The state has also put forward higher requirements on the energy saving, environmental protection and fire safety of building exterior wall insulation in terms of policies. Aerogel materials are considered to be the most promising thermal insulation materials in the future due to their excellent thermal insulation properties and fire resistance. In this paper, the preparation process and application of aerogel inorganic cementitious composites were investigated, mainly aerogel cement composites and aerogel gypsum composites. We analyzed the recent research results, and focused on the preparation optimization and application prospects of aerogel inorganic cementitious composites. In the preparation of aerogel inorganic cementitious composites, many researchers have proposed different preparation methods to optimize the interface between aerogel and inorganic cementitious materials in order to avoid the strength degradation caused by doping aerogel. At present, preparing aerogel into aerogel slurry for compounding is considered to be a relatively optimal incorporation method. It is found that aerogel inorganic cementitious composites have great prospects for thermal insulation applications in the construction field. However, due to the high cost of aerogel preparation and the poor interfacial bonding between aerogel and inorganic cementitious materials, the application of aerogel in building thermal insulation is limited. This paper has reference significance for studying the application of aerogel in the construction industry.